1994
DOI: 10.1007/bf00193477
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin does not alter the effects of oral midazolam on human performance

Abstract: Since macrolide antibiotics inhibit the oxidative hepatic metabolism of various drugs, including midazolam, the present double blind studies were conducted to find out if azithromycin, a new macrolide of the azalide type, would inhibit the metabolism of midazolam and enhance the effects of midazolam on human performance. In Study I, 64 healthy medical students, divided in four parallel groups received placebo, midazolam (10 mg or 15 mg), and midazolam 10 mg combined with azithromycin (500 mg + 250 mg). In Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Since some macrolides inhibit oxidative hepatic metabolism of various drugs, several studies have been conducted with the combination of AZM and midazolam [197–200]. A total of 64 healthy volunteers were included in a double-blinded randomized trial comparing the effect of co-administration of midazolam with AZM or ERY.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since some macrolides inhibit oxidative hepatic metabolism of various drugs, several studies have been conducted with the combination of AZM and midazolam [197–200]. A total of 64 healthy volunteers were included in a double-blinded randomized trial comparing the effect of co-administration of midazolam with AZM or ERY.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 64 healthy volunteers were included in a double-blinded randomized trial comparing the effect of co-administration of midazolam with AZM or ERY. The authors concluded that ERY, and not AZM, enhanced the objective and subjective effects of midazolam via interference of AZM with the hepatic CYP3A metabolism of midazolam [200]. A double-blind 2-phase cross-over study of 10 healthy volunteers contradicts these findings, as no changes in PD or PK of midazolam were found except for a decrease in C max by 44% and a delay in t max from 1.0 to 1.25 hours [199].…”
Section: Resultsmentioning
confidence: 99%
“…More modest changes (two-to fourfold) were found following a single dose of grapefruit juice (181) and a period of erythromycin (161), clarithromycin (227), roxithromycin (228), fluconazole (144), or diltiazem (131) administration. By contrast, several days pretreatment with azithromycin (229)(230)(231) and terbinafine (226) had no effect on midazolam's metabolism. Thus, at the present time, measurement of changes in midazolam's clearance and the fractional clearance associated with the 1 -hydroxy pathway of metabolism after oral drug administration probably provides the best means by which quantitative alterations in intestinal and/or hepatic CYP3A resulting from a drug interaction activity can be determined in vivo.…”
Section: In Vivo Probes Of Cyp3a Activitymentioning
confidence: 86%
“…This is especially the case when inhibition of metabolism occurs, since this often results in increased sedative effects. Thus, azole antifungal agents, some but not all macrolides, selective serotonin reuptake inhibitors, and calcium-channel antagonists such as verapamil and diltiazem have been shown to markedly enhance plasma levels of midazolam (131,139,144,161,200,(226)(227)(228)(229)(230)(231), triazolam (132,(265)(266)(267)(268), and alprazolam (268)(269)(270)(271)(272). Moreover, central nervous effects were increased and their duration prolonged.…”
Section: Benzodiazepinesmentioning
confidence: 99%
“…MDZ was found to have less interaction with roxythromycin 55,56 and no interaction with azithromycin. 51, 57 Effects of nefazodone, fluoxetine, and fluvoxamine on the pharmacokinetics of a single oral 10 mg dose of MDZ were investigated together in a randomized parallel study that used ketoconazole as a positive control. 58 Fluoxetine (60 mg/day for 5 days, then 20 mg/day for 6 days) and fluvoxamine (titrated to 200 mg/day) had no significant effect on MDZ, while nefazodone (titrated to 400 mg/day) and ketoconazole (200 mg/day for 11 days) increased AUC of MDZ to 4.8-fold and 11.7-fold of the baseline values, respectively.…”
Section: Metabolism-based Drug Interactionsmentioning
confidence: 99%